Optimization of hydrolysis process using empty fruit bunches by locally produced cellulases - Zainan, Nur Hidayah; Alam, Md. Zahangir; Al-Khatib, Ma An Fahmi Rashid (2011)
The utilization of lignocellulosic materials for bioethanol production such as empty fruit bunches (EFB) from palm oil plant attract increasing attention as an abundantly available and cheap renewable residue especially in Malaysia where palm oil production is the major agricultural industry. The most challenging part in conversion of lignocellulosic materials to bioethanol is the hydrolysis process in order to obtain reducing sugar. In this study, cellulase enzyme used for the hydrolysis was produced from palm oil mill effluent (POME), whose cost of production was considerably low compared to commercial cellulases. The hydrolysis of EFB for sugar production as an initial step was statistically optimized based on agitation speed, EFB and cellulase concentrations using Response Surface Methodology (RSM)/ Box-Behnken design in 2L Bioreactor. The design contains a total of 17 experimental runs and data obtained from RSM on reducing sugar production were subjected to the analysis of variance (ANOVA) and analyzed using a second order polynomial equation. Maximum sugar production was realized after three days hydrolysis. The amount of sugar produced showed an economic feasibility of using EFB as a renewable raw material for bioethanol production.